Evaluation of the Implementation of School Financial Management in the Free School Program Using the Stake Model at Senior High School - Saipul Annur; Afriantoni Afriantoni; Asih Wahyu Rini (Journal Evaluation in Education (JEE), 2025)
Purpose of the Study: This study evaluates the implementation of school financial management within the free school program at Senior High School 3 Palembang using the Stake evaluation model to assess effectiveness, transparency, and accountability in fund management. As education funding is crucial in ensuring equal learning opportunities, examining how financial resources are managed within tuition-free programs is essential for sustainable policy implementation. Despite regulatory guidelines, financial management in free school programs often encounters obstacles in coordination, supervision, and transparency. Methodology: This research adopts a qualitative case study approach, utilizing interviews, observations, and document analysis to gather in-depth insights. The Stake model framework evaluates the program through four dimensions: context, input, process, and product. Main Findings: Findings reveal that while financial management at Senior High School Palembang adheres to procedural standards, significant challenges persist in supervision mechanisms and budget reporting. Inefficiencies in fund allocation and monitoring impact the program’s effectiveness, highlighting the need for improved financial literacy among administrators and enhanced accountability measures. Novelty/Originality of the Study: The novelty of this study lies in its application of the Stake model to assess financial governance in free school programs, a relatively unexplored area in education management research. By providing a localized evaluation, this study enriches existing literature and offers practical recommendations for policymakers, school administrators, and education stakeholders. Strengthening financial transparency and accountability is crucial to ensuring that free education programs fulfill their intended objectives, fostering equitable access to quality education while maintaining fiscal responsibility.